Privacy in the use of drones for journalistic purposes. Regulatory frameworks of the United States and Europe - Aguado-Guadalupe, Guadalupe (2021)
This article analyzes the repercussions on journalistic activity of the regulatory measures adopted by the United States and Europe to protect privacy in the use of drones. Similarities and differences between the adopted regulations are evaluated. It is observed that in the United States recommendations are generally chosen, in which drone user´s willingness prevails over third parties´ right to privacy. However, there are exceptions, such as the cases of the states of Texas and California, where the use of drones without proper authorization is considered a violation of the right to privacy. In Europe, the regulations are applicable to all member countries, and the system provides more guarantees, considering the principles of necessity and transparency.